TRADISI RUWATAN WAYANG BAGI UMAT HINDU JAWA - Poniman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
The existence of Wayang Kulit is a traditional Javanese art in particular, which is closely related to the levels of human life or life cycle. Humans in their lives can be bound by norms or value systems adopted by their people. The norms that still apply in Javanese society include ruwatan ceremonies that contain elements of human salvation or cleansing from existing sins and calamities. Some people who belong to sukerta (dirty, sinful) according to Javanese beliefs must be renewed. Because if it is not renewed it will be the prey of Batara Kala. So through ruwatan by performing wayang kulit, the Murwakala story and the reading of ruwatan mantras, the Javanese people believe that they will not be afraid and unlucky in their future lives.